2015
DOI: 10.1136/bmjqs-2015-004226
|View full text |Cite
|
Sign up to set email alerts
|

Remote video auditing with real-time feedback in an academic surgical suite improves safety and efficiency metrics: a cluster randomised study

Abstract: ImportanceCompliance with the surgical safety checklist during operative procedures has been shown to reduce inhospital mortality and complications but proper execution by the surgical team remains elusive.ObjectiveWe evaluated the impact of remote video auditing with real-time provider feedback on checklist compliance during sign-in, time-out and sign-out and case turnover times.Design, settingProspective, cluster randomised study in a 23-operating room (OR) suite.ParticipantsSurgeons, anaesthesia providers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
0
38
0
2
Order By: Relevance
“…It has also been suggested that when used routinely, video could be used to investigate adverse events. [4][5][6] What has gone relatively unnoticed in these recent discussions about the potential of video in the operating room is the possibilities it opens up for empirical research. While videos can only provide a partial representation of what happened and are always open to interpretation, they do provide a relatively objective, shareable point of reference.…”
Section: Video Recording In the Operating Roommentioning
confidence: 99%
“…It has also been suggested that when used routinely, video could be used to investigate adverse events. [4][5][6] What has gone relatively unnoticed in these recent discussions about the potential of video in the operating room is the possibilities it opens up for empirical research. While videos can only provide a partial representation of what happened and are always open to interpretation, they do provide a relatively objective, shareable point of reference.…”
Section: Video Recording In the Operating Roommentioning
confidence: 99%
“…Overdyk et al 5 demonstrate the potential of using video-derived data to improve compliance rates. The authors, based at Hofstra North Shore-LIJ School of Medicine, performed a prospective study in which surgeons and other OR staff were randomised to video monitoring with real-time feedback on key patient safety activities, including compliance with the safety checklist during sign-in, time-out and sign-out procedures.…”
mentioning
confidence: 99%
“…This approach offered the advantage of real time auditing of clinical care by remote staff managed completely by the third party company. 1214 …”
Section: Discussionmentioning
confidence: 99%